2020
DOI: 10.1111/tan.14054
|View full text |Cite
|
Sign up to set email alerts
|

Toward defining the immunogenicity of HLA epitopes: Impact of HLA class I eplets on antibody formation during pregnancy

Abstract: Eplets are functional units of structural epitopes on donor HLA, potentially recognized by complementarity‐determining regions of the paratope of the recipients' B‐cell receptors or antibodies (Ab). Their individual immunogenicity is poorly described, yet this feature would be of clinical importance for pretransplant risk assessment. The aim of this study was to determine the relative immunogenicity of HLA class I eplets in the pregnancy setting, where mismatched eplets are present on paternal HLA antigens of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 26 publications
0
32
1
Order By: Relevance
“…So far, most investigators either reduced the complexity by focusing only on antibody-verified eplets or selected the putative target based on the simplest eplet combination, which was regarded as the most likely one. 9,23,24 Therefore, such approaches have inherent biases. In this study, we aimed to explore the immunogenicity of all HLA-DQ eplets in an unbiased manner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, most investigators either reduced the complexity by focusing only on antibody-verified eplets or selected the putative target based on the simplest eplet combination, which was regarded as the most likely one. 9,23,24 Therefore, such approaches have inherent biases. In this study, we aimed to explore the immunogenicity of all HLA-DQ eplets in an unbiased manner.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it is very challenging to clearly determine the targeted eplet based on an antibody reaction pattern. So far, most investigators either reduced the complexity by focusing only on antibody‐verified eplets or selected the putative target based on the simplest eplet combination, which was regarded as the most likely one 9,23,24 . Therefore, such approaches have inherent biases.…”
Section: Discussionmentioning
confidence: 99%
“…Eplet incompatibility predicts the potential for immune‐mediated injuries, and efforts are underway to identify the most immunogenic eplets (Hönger et al., 2020). Risk of immune‐mediated injuries may be accentuated with re‐exposure to similar HLA eplets.…”
Section: Roadmap To Implementation Of Eplet Matching—challenges and Omentioning
confidence: 99%
“…Subsequent studies which relied on cytotoxic assays later determined the prevalence and timing of pregnancyinduced anti-HLA antibody (4)(5)(6). The advent of singleantigen bead technology has greatly improved detection methods and revealed that pregnancy elicits a paternal HLAreactive antibody response in 50-84% of mothers in the first year after pregnancy that may have HLA epitope bias (6)(7)(8)(9)(10)(11)(12). As in other types of immune exposures, the number of times that a woman is exposed to fetal alloantigen matters, as multiparous females have a higher incidence of paternal HLA-reactive antibodies (7) with strong binding to HLA epitopes (13).…”
Section: Clinical Impact Of Pregnancy Sensitizationmentioning
confidence: 99%